Optimized Combustion Synthesis and Characterization of Nanostructured Ba2RESbO6 Perovskites - Rajan, Jose; Nair, V. M.; Rajul, K.; Wariar, P. R. S. (Penerbit Universiti Malaysia Perlis, 2014)
Combustion of citrate complex has been a popular choice to synthesize nanocrystals of transition metal oxides in a single-step process. The amount of citric acid used for combustion is conventionally calculated based on the total valence of the oxidizing and reducing agents while keeping the equivalent ratio unity such that combustion energy is a maximum. This chapter demonstrates by employing quantum chemical calculations that the amount of citric acid could be reduced to nearly half if prepared for appreciable amounts. Transition metal oxides belong to quaternary double perovskites, with general formula Ba2 RESbO6 (RE=Rare-earth), have been synthesized as nanocrystals as examples to validate the calculations.